Probiotics and probiotic-based vaccines: A novel approach for improving vaccine efficacy - Kazemifard, Nesa; Dehkohneh, Abolfazl; Baradaran Ghavami, Shaghayegh (Frontiers in Medicine, 2022)
Vaccination is defined as the stimulation and development of the adaptive immune system by administering specific antigens. The efficacy of vaccines in inducing immunity is varied in different societies due to economic, social, and biological conditions. One of the influential biological factors is gut microbiota. Cross-talks between gut bacteria and the host immune system are initiated at birth during microbial colonization and directly control the immune responses and protection against pathogen colonization. On the other hand, imbalances in the gut microbiota composition, termed dysbiosis, can trigger several immune disorders through the activity of the adaptive immune system and impair the adequate response to the vaccination. Probiotics are part of the gut microbiota composition, which has health benefits for the host. Probiotics are generally consumed as a component of fermented foods and affect both innate and acquired immune systems and decrease infections. This review aimed to discuss the gut microbiota's role in regulating immune responses to the vaccination and how probiotics can help induce immune responses against pathogens. Finally, probiotic-based oral vaccines and their efficacy have been discussed in the last section.